Overview of brown bast syndrome of Hevea brasiliensis - Nik Hashim, Nik Hashyati; Sulaiman, Zulkefly; Tengku Muda Mohamed, Mahmud; Abd Samad, Mohd Yusoff (Universiti Putra Malaysia Press, 2018)
Hevea brasiliensis is one of the popular industrial crops in Malaysia better known as rubber tree belongs to the family Euphorbiaceace. From more than 12 species of Hevea, only Hevea brasiliensis is economically exploited because the milky latex extracted from the tree is the primary source of natural rubber. As in other crops, various plant physiological conditions and pathogenic diseases influence rubber production. Brown bast is one of the most serious threats to natural rubber production. In general, high-yielding clones of rubber tree are often considered to be more susceptible to this physiological disorder also commonly termed Tapping Panel Dryness (TPD). It is estimated that brown bast leads to approximately 15-20% decrease in yield. There is no known cure for brown bast yet. However, many plantation practices manage brown bast in rubber by giving tapping rest and changing tapping panel. Hence, this review condenses the causal of brown bast, symptoms of diseases and also control of brown bast affected Hevea tree.